(untitled) (Per Musi, 2023)
Higher music studies present a lack in terms of the use of active methodologies that are relevant in current teaching. This article is systematized with the main objective of evaluating the incorporation of educational innovation program in teachings with artistic characteristics. To do this, a qualitative methodology has been used from carrying out an intervention on higher education students specializing in percussion, taking as reference the pieces for percussion ensemble by the composers Amadeo Roldán and Edgar Varèse. The results obtained provide data that project the suitability of application of these methodological innovations. The final considerations reflect the achievement of greater and diverse objectives by the experimental group compared to the group in which traditional teaching has been applied. This intervention has contributed to the opening of new fields of research within musical didactics.